Low refractive index resin composition for TPP nano 3D printing and photonic wire bonding method using the same
A low-refractive index resin composition for TPP nano 3D printing addresses defects in photonic wire bonding by using a two-step process to form optical waveguides, enhancing the accuracy and reliability of photonic integrated circuits.
Patent Information
- Application Number
- JP2024525771
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-11-28
- Filing Date
- 2022-12-01
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2042-12-01
AI Technical Summary
Conventional photonic wire bonding methods face issues with defects such as damage to optical waveguides and changes in bonding positions due to the high viscosity and shrinkage of high-refractive index resins, leading to inaccuracies in connecting optical elements in photonic integrated circuits.
A low-refractive index resin composition for TPP nano 3D printing, comprising 30-70% perfluorinated monomer, 10-40% fluorinated acrylate oligomer, and 0.5-2.0% TPP reaction initiator, is used to form optical waveguides with improved adhesion and durability, minimizing defects through a two-step photonic wire bonding process.
The method enhances the accuracy and reliability of photonic integrated circuits by precisely connecting optical elements with reduced light loss and defects, ensuring high reliability and improved bonding strength.
Smart Images

Figure 2025501851000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a low refractive index resin composition for TPP nano 3D printing and a photonic wire bonding method using the same, and more particularly to a fluorinated resin composition having a low refractive index containing a (meth)acrylic reactive group that can be applied to a nano 3D printing method using a two-photon polymerization (TPP) reaction, and a photonic wire bonding (PWB) method that minimizes optical loss by directly forming an optical waveguide clad surrounding a micro-sized single-mode optical waveguide core on a circuit board by the TPP nano 3D printing method, thereby supporting the fabrication of a highly reliable photonic integrated circuit (PIC). [Background technology]
[0002] Two-photon polymerization (TPP) is a nonlinear photopolymerization reaction that occurs when two photons are simultaneously absorbed by a medium when light with energy lower than the energy gap between the ground state and the exited state of the medium is incident and the amount of incident light is higher than a certain level. It is a technology used in 3D printing of nanostructures using the Laser Direct Writing (LDW) method, which focuses light emitted from a low-energy light source such as infrared light in a preselected space at a specific position to increase the amount of light (i.e., energy density) and selectively harden the space where the light is focused.
[0003] Such Laser Direct Writing (LDW) 3D printing is usually performed by continuously changing the focal position of an objective lens using an optical system to focus light on a preset accurate target position to create nanostructures of a desired shape. In particular, as disclosed in U.S. Patent No. 9,034,222, it is a nano 3D printing technology that is mainly used for Photonic Wire Bonding (PWB), which forms an optical waveguide connecting optical elements mounted on a chip in the process of manufacturing a silicon photonics-based Photonic Integrated Circuit (PIC), in which various optical elements are integrated on a single chip.
[0004] Here, the optical elements mounted on the PIC manufactured by the above method are usually spaced apart by several hundred μm, and the optical waveguide connecting them is designed to have a diameter of several μm or less to maintain a single mode. Therefore, the wire structure (i.e., optical waveguide) formed in this way is relatively vulnerable to external impact and / or changes in the surrounding environment such as temperature and humidity, and for passivation of such a wire structure, the optical waveguide and its surroundings are covered with a low-refractive light-curing resin and cured, which acts as a cladding for the optical waveguide and protects the optical waveguide from external impact and changes in the surrounding environment. The passivation of such an optical waveguide is performed by applying a low-refractive resin having a viscosity of several thousand cPs on a PIC chip on which an optical element and an optical waveguide are formed, and curing the resin.
[0005] However, optical elements such as optical modulators, photodetectors, optical multiplexers, and optical couplers that make up the above-mentioned photonic integrated circuit (PIC) are usually mounted on a circuit board with a thickness (height) of several hundred μm or more, and in most cases, their mounting positions are also spaced several hundred μm or more from the bottom surface of the board. The optical input / output parts of these elements are generally formed at a position several hundred to several thousand μm or more away from the bottom surface of the board. As a result, the optical waveguides connecting these optical input / output parts must also be formed at a position several hundred to several thousand μm or more away from the bottom surface of the board, leaving an empty space of several hundred to several thousand μm between the upper part of the bottom surface of the board and the optical waveguide.
[0006] As explained above, in the process of applying a high-viscosity low-refractive index resin with a viscosity of several thousand cPs onto a PIC chip, the connection state of the optical waveguide formed between optical elements is often damaged due to the friction and surface tension of the high-viscosity resin as well as the load of the applied resin. In addition, as the applied low-refractive index resin hardens, its volume shrinks, causing a change in the connection position of the optical waveguide formed between optical elements. This change in position of the photonic wire bonding (PWB) is a critical issue that must be resolved, especially in the case of single-mode optical element connections, which require a marginal tolerance of at least 0.5 μm. Summary of the Invention [Problem to be solved by the invention]
[0007] The present invention aims to provide a new and improved photonic wire bonding (PWB) method and a low refractive index resin composition that can be effectively used therefor, so as to fabricate a photonic integrated circuit (PIC) having improved optical efficiency and high reliability by minimizing the occurrence of defects during the manufacturing process, such as damage to an optical waveguide and / or changes in bonding position caused by a low refractive index resin applied to a circuit board for passivation of the optical waveguide in the above-mentioned conventional photonic wire bonding (PWB) process for forming a photonic integrated circuit (PIC). [Means for solving the problem]
[0008] In order to achieve the above-mentioned object, the present invention provides a low refractive index resin composition for TPP nano 3D printing, which is composed of 30 to 70 wt% perfluoroether oligomer, 8 to 30 wt% fluorinated monomer, 10 to 40 wt% fluorinated (meth)acrylate oligomer, and 0.5 to 2.0 wt% photoinitiator for TPP reaction and can be effectively used in a nano 3D printing method using a two-photon photopolymerization (TPP) reaction, and at the same time, presents an improved and effective photonic wire bonding (PWB) method that can be used to fabricate optical integrated circuits (PICs) with improved optical efficiency and high reliability. Effect of the Invention
[0009] The low refractive index resin composition for optical waveguide cladding manufactured by the present invention provides sufficient solubility for photoinitiators for TPP reaction, thereby helping to precisely form the cladding of an optical waveguide that connects optical elements by TPP-based photonic wire bonding using a 3D nanoprinter during the process of manufacturing photonic integrated circuits (PIC).
[0010] In addition, the photonic wire bonding (PWB) method proposed in the present invention has the effect of dramatically improving the accuracy and reliability of the manufactured photonic integrated circuit (PIC) by assisting in forming the optical waveguide core connecting the optical elements provided on the substrate and the optical waveguide clad surrounding the core using a 3D nanoprinter by a TPP-based photonic wire bonding (PWB) method using light irradiation. [Brief description of the drawings]
[0011] [Figure 1] FIG. 2 is a diagram showing a schematic diagram of a core and a cladding of an optical waveguide constituting a photonic wire bonding (PWB) formed according to the present invention. [Diagram 2] 2 is a diagram for explaining the shape of the optical waveguide core shown in FIG. 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, the photonic wire bonding method performed by the TPP nano 3D printing process according to the present invention and the low refractive index resin composition used to form the optical waveguide clad in the process will be described in more detail with reference to several examples.
[0013] As briefly explained above, conventionally, in producing an optical integrated circuit (PIC) using photonic wire bonding (PWB), first, a resin composition for a high refractive index optical waveguide core for forming an optical waveguide between optical elements mounted on a substrate is dropped, and then an optical waveguide core for connecting the optical elements is printed by irradiating light according to a pre-designed pattern using a 3D nanoprinter, and then a low refractive index resin composition for an optical waveguide clad in an amount sufficient to cover the entire printed optical waveguide including the connecting portion of the optical elements is dropped and cured to form an optical integrated circuit (PIC).
[0014] However, in the manufacturing process of such conventional photonic integrated circuits (PICs), as explained above, during the dropping and curing process of the low refractive index resin composition for cladding, defects such as damage to the optical waveguide core printed on the substrate and / or changes in bonding position often occur due to the load and surface tension of the applied low refractive index resin composition and / or the contraction force during the curing process.
[0015] The present invention is intended to fundamentally solve the problems of the conventional technology. In the present invention, two-photon photopolymerization is performed between optical elements mounted on a circuit board. The present invention provides an improved photonic wire bonding (PWB) method that minimizes defects during the manufacturing process and can fabricate an optical integrated circuit (PIC) with improved optical efficiency and reliability by coating a low refractive index resin composition that can be polymerized (TPP) and then printing a lower clad that serves to fix a connection portion between an optical element and an optical waveguide while guiding an area where an optical waveguide connecting an optical element is to be printed by selective light irradiation using a TPP-based nano 3D printing method, coating a high refractive index resin composition for forming an optical waveguide core on the printed lower clad again, printing a high refractive optical waveguide core in the optical waveguide printing area formed in the lower clad using the TPP-based nano 3D printing method, and finally printing an upper clad on the upper clad again using the TPP-based nano 3D printing method of the same type. EXAMPLES
[0016] In order to realize the photonic wire bonding (PWB) method of the present invention as described above, first and foremost, a resin composition that is capable of the two-photon photopolymerization (TPP) reaction described above, has a low refractive index suitable for a single-mode optical waveguide clad, and at the same time, has excellent adhesion to optical elements, must be provided.
[0017] That is, the low refractive index resin composition applied to the realization of the present invention is 1) It can provide sufficient solubility for photopolymerization initiators for two-photon polymerization (TPP) reactions, 2) After curing, it has a low refractive index of at least 1.400 or less; 3) It must exhibit excellent adhesion to silicon, quartz, metals, etc.
[0018] More specifically, to realize TPP-based 3D nanoprinting, the two-photon photopolymerization initiator for the TPP reaction must have sufficient solubility so that it can be sufficiently dissolved and mixed in the resin composition. However, in order for a photonic wire (i.e., optical waveguide core) with a diameter of 2 μm having a refractive index of at least 1.5 to transmit and receive optical signals of terabytes or more in single mode while effectively suppressing optical loss due to the generation of optical signals in higher modes, the refractive index of the cladding must be at least 1.400 or less, and preferably 1.375 or less.
[0019] Therefore, in order to realize a clad with such a low refractive index, a resin composition applied for optical fiber clad generally uses a resin containing 40 wt% or more of fluorine. However, at this time, resins such as perfluoro ether, fluorinated siloxane, and fluorinated acrylic, which contain such a high content of fluorine, do not mix well with general hydrocarbon compounds due to their low surface tension and high density, which causes a problem that the two-photon photopolymerization initiator for the TPP reaction does not dissolve sufficiently in the above-mentioned resin composition for clad.
[0020] In particular, to realize 3D nanoprinting based on the TPP reaction, the photoinitiator for TPP must be contained in an amount of at least 1.0 wt% of the total weight of the resin composition. However, most of the photoinitiators for TPP that are commonly used are composed of a hydrocarbon structure with a high molecular weight containing multiple benzene rings, and as described above, they are hardly dissolved or mixed into low-refractive index photocurable resin compositions that contain a large amount of fluorine, making it difficult to realize the two-photon photopolymerization (TPP) reaction.
[0021] In order to solve these problems, the present invention improves the solubility of the photoinitiator by synthesizing a resin composition by mixing the low refractive index fluorinated oligomer described above with a photoinitiator for TPP, which has a high molecular weight hydrocarbon group and all of which have a (meth)acrylic group and a fluorinated carbon group of a hydrocarbon structure, and a fluorinated monomer that acts as a co-solvent for the low refractive index photocurable resin with a high fluorine content.
[0022] Furthermore, in order to improve the physical properties of the resin composition for cladding made of the above-mentioned low refractive index fluorinated oligomer and fluorinated monomer, and at the same time increase the adhesive force with silicon, quartz, metal, etc., and improve the bonding strength with optical elements, a resin composition containing a fluorinated (meth)acrylic having a methoxy (ethoxy) silane reactive group has been synthesized, thereby developing a resin composition for optical fiber cladding that helps photonic wire bonding (PWB) formed on a circuit board to be more firmly connected to optical elements and improves the durability of photonic integrated circuits (PICs) formed on the circuit board.
[0023] Hereinafter, the specific compositional components of the low refractive index resin composition for TPP nano 3D printing according to the present invention developed through the above-mentioned process will be described.
[0024] The low refractive index resin composition for TPP nano 3D printing according to the present invention is i) 30-70 wt% perfluoroether oligomer for low refractive index properties; ii) 8-30 wt% of fluorinated monomer to improve the solvency of the photoinitiator for the TPP reaction; iii) 10 to 40 wt % of a fluorinated acrylate oligomer for improving the physical properties of the resin composition and increasing the adhesive strength with optical elements, and iv) Contains 0.5 to 2.0 wt % of a photoinitiator for the TPP reaction.
[0025] i) Perfluoroether oligomers for low refractive index properties The perfluoroether oligomer used in the synthesis of the low refractive index resin composition for TPP nano 3D printing according to the present invention is a polysiloxane oligomer already developed by the applicant of the present invention, and its specific structural formula is as shown in Chemical Formula 1 below (see Korean Patent Publication No. 10-2016-0137929, “Polysiloxane oligomer, polysiloxane copolymer and manufacturing method thereof”).
[0026] [ka] Where: R 1 are each independently a hydrocarbon (CH 2 ) 2 to 10 (meth)acrylate groups, R 2 are each independently -CH 2 O- or -CH 2 (OCH 2 CH 2 ) a O- (where a is an integer from 1 to 3), R 3 is an aromatic or aliphatic hydrocarbon group having 6 to 20 carbon atoms, R 4 are each independently -CH 2 -, -CH 2 CH 2 -or-CH 2 (OCH 2 CH 2 ) a - (a is an integer between 1 and 10), m, o, p, q and r are the repeat numbers for each repeat unit, m and o are each 1 to 6; r is from 1 to 5,000; p is 1 to 20; The ratio of p to q (p / q) is in the range of 0.8 to 2.5.
[0027] As a result of experiments using Luvantix ADM's DHBO32, DMO, D9MOPEG200 and DHGO34 products, which are commercial resin compositions having the structure of Chemical Formula 1, it was confirmed that all of these resin compositions exhibit a low refractive index of 1.375 or less after curing, and have low refractive index characteristics suitable for the cladding of optical waveguides.
[0028] However, as a result of compatibility experiments with various types of photoinitiators for the TPP reaction, it became clear that the above-mentioned perfluoroether oligomer alone does not exhibit sufficient dissolving power for the photoinitiators for the TPP reaction, and therefore it was confirmed that an additional composition is required to improve the dissolving power for the photoinitiators for the TPP reaction.
[0029] Here, the above-mentioned perfluoroether oligomer is a composition contained in the resin composition to realize low refractive index characteristics required for the clad of an optical waveguide, and the composition of the present invention is not necessarily limited thereto. Of course, various fluorinated oligomers such as fluorinated siloxane having the structure of the following Chemical Formula 2 disclosed in the above-mentioned Patent Publication No. 10-2016-0137929 can be used.
[0030] [ka] Where: R 1 are each independently a hydrocarbon (CH 2 ) 2 to 10 (meth)acrylate groups, R 2 represents a hydrogenated or fluorinated carbon group having 2 to 20 carbon atoms; R 3 is an alkoxysilane group having 1 to 5 silicon atoms; l, m, n and o are repeat numbers for each repeat unit and all range from 1 to 5,000.
[0031] ii) Fluorinated monomers to improve the solvency of photoinitiators for the TPP reaction As explained in i) above, it was confirmed that the perfluoroether oligomer alone, which is used to impart low refractive index properties to the resin composition, does not have sufficient dissolving power for the photoinitiator for the TPP reaction. Therefore, in the present invention, the solubility of the photoinitiator is improved by synthesizing a resin composition by mixing a TPP photoinitiator consisting of a high molecular weight hydrocarbon group and a fluorinated monomer having both a (meth)acrylic group and a fluorinated carbon group in a hydrocarbon structure to act as a co-solvent capable of dissolving all of the perfluoroether oligomer having a high fluorine content.
[0032] Examples of such fluorinated monomers include (the percentage in parentheses is the fluorine content (wt%) in the monomer), 2,2,2-trifluoroethyl acrylate (2,2,2-Trifluoroethyl Methacrylate, 37%), 2,2,2-trifluoroethyl methacrylate (2,2,2-Trifluoroethyl Methacrylate, 34%), 2,2,3,3-2,2,3,3,3-Pentafluoropropyl Methacrylate (2,2,3,3-2,2,3,3,3-Pentafluoropropyl Methacrylate, 41%), 2,2,3,3-Tetrafluoropropyl Methacrylate (2,2,3,3-Tetrafluoropropyl Methacrylate, 38%), 2,2,3,3,3-Pentafluoropropyl Methacrylate ( ... Methacrylate, 44%), 1H,1H,5H-Octafluoropentyl Acrylate, 53%), 1H,1H,5H-Octafluoropentyl Methacrylate, 51%), 1,1,1,3,3,3-Hexafluoroisopropyl Acrylate, 51%), 2,2,3,4,4,4-Hexafluorobutyl Methacrylate, 46%), 1,1,1,3,3,3-Hexafluoroisopropyl Methacrylate, 52%), 2,2,3,3,4,4,4-Heptafluorobutyl Methacrylate (50%), 1H,1H,2H,2H-Nonafluorohexyl Acrylate (54%), 1H,1H,2H,2H-Nonafluorohexyl Methacrylate (1H,1H,2H,2H-Nonafluorohexyl Methacrylate, 52%), 2,2,3,3,4,4,5,5,6,6,7,7-Dodecafluoroheptyl Acrylate, 59%), 2,2,3,3,4,4,5,5,6,6,7,7-Dodecafluoroheptyl Methacrylate, 57%), 1H,1H,2H,2H-Tridecafluoro-n-octyl Acrylate, 1H,1H,2H,2H-Tridecafluoro-n-octyl Acrylate, 59%), 1H,1H,2H,2H-Tridecafluoro-n-octyl Methacrylate, 57%), 1,6-Bis(acryloyloxy)-2,2,3,3,4,4,5,5-octafluorohexane, 41%), 2-Perfluorooctyl ethyl acrylate, 62%), 2-Perfluorodecyl ethyl acrylate, 65%), and 2-Perfluorooctyl ethyl methacrylate, 61%).
[0033] Here, the fluorine content of the fluorinated monomer is more advantageous in lowering the refractive index of the resin composition as the value of the fluorine content increases, but the dissolving power of the fluorinated monomer in the TPP photoinitiator decreases.
[0034] The following <Test Example 1> is a test to find a fluorinated monomer that can provide sufficient dissolving power for a photoinitiator for TPP in the resin composition according to the present invention. The DMO and DHGO34 resins of Luvantix ADM, selected from the perfluoroether oligomer materials described above, were mixed with various fluorinated monomers exemplified above in a weight ratio of 10% to 30%, and then a dissolving power test for a photoinitiator for TPP was performed.
[0035] The photoinitiators used in the test were a bis-triazole-based initiator (initiator #1) having the structure of the following Chemical Formula 3 and a benzylamine-based initiator (initiator #2) having the structure of Chemical Formula 4.
[0036] [ka]
[0037] [ka]
[0038] [Table 1]
[0039] <Test Example 1> Comparison of the dissolving power of photoinitiators depending on the type of fluorinated monomer, the composition content of the resin composition, and the fluorine content (wt%) contained in the monomer (○: Clear, X: Haze) As confirmed from the above <Test Example 1>, when the fluorine content of the fluorinated monomer is 60 wt% or more, the dissolving power for the photoinitiator is rapidly reduced and the photoinitiator shows a haze precipitation state in the resin composition, making it unsuitable for use as a co-solvent. Therefore, in the present invention, when forming a low refractive index resin composition for TPP nano 3D printing, only fluorinated monomers having a fluorine content of 30 to 60 wt% are selectively applied.
[0040] In addition, through various similar tests, it was confirmed that when the fluorinated monomer contained in the resin composition is in the range of 8 to 30 wt%, the resin composition can provide sufficient dissolving power for the TPP photoinitiator.
[0041] Furthermore, in the above test examples, a bis-triazole-based initiator (initiator #1) and a benzylamine-based initiator (initiator #2) were used, but the initiators applicable to the present invention are not necessarily limited thereto. Of course, various photoinitiators including aminostyryl-triazine-based initiators, imidazole-based initiators, benzyl morpholino phenyl-based initiators, bengal-based initiators, erythrosine-based initiators, isopropylthioxan-based initiators, thienyl coumarin-based initiators, and diphenyl phosphine-based initiators can be used.
[0042] iii) Fluorinated acrylate oligomers for improving the physical properties of the resin composition and increasing the adhesion to optical elements In the present invention, as described above, in order to improve various properties of the resin composition of the present invention, which plays the role of a clad of an optical waveguide by photonic wire bonding (PWB), and at the same time increase adhesion to silicon, quartz, metal, etc., and improve bonding strength with an optical element, a fluorinated (meth)acrylic having a methoxy (ethoxy) silane reactive group is contained in the resin composition to be manufactured. In this case, the fluorinated (meth)acrylic used in the synthesis of the low refractive index resin composition for TPP nano 3D printing according to the present invention is also a fluorinated acrylate oligomer already developed by the applicant of the present invention, and its specific structural formula is as shown in Chemical Formula 5 below (see Korean Patent Registration No. 10-2353598, "Poly (meth) acrylate copolymer and resin composition for optical fiber clad based thereon").
[0043] [ka] Where: k, l, m, and n are constants each having a value between 0 and 10,000; R is -H, -CH 3 or a hydrocarbon group having 20 or less carbon atoms, R f is fluorinated carbon (-CF 2 -, -CF 3 ) is a fluorinated carbon group having 2 to 40 carbon atoms, F 1 is a hydrocarbon group having 2 to 40 carbon atoms containing at least one (meth)acrylate, vinyl or epoxy reactive group, F 2 contains 1 to 3 methoxy reactive groups (-OCH 3 ) or ethoxy reactive group (-OCH 2 CH 3 ), F 3 is a hydrocarbon group that does not react in a urethane bonding reaction and has 2 to 40 carbon atoms, in which some of the bonded hydrogens (H) are replaced with oxygen (O) or nitrogen (N).
[0044] The above-mentioned fluorinated acrylate oligomer is included in the resin composition in an appropriate ratio depending on the various physical property requirements required for the low refractive index resin composition for TPP nano 3D printing to be produced, and the resin composition according to the present invention contains 10 to 40 wt% of the fluorinated acrylate oligomer.
[0045] Here, the characteristics of each reactive group constituting the fluorinated acrylate oligomer will be described in more detail. 1F 1 (Meth)acrylate reactive groups for improving the physical properties of the resin composition In order for the optical waveguide cladding formed by TPP3D nanoprinting to meet the various environmental conditions required for optical device components, it must have a low refractive index to maintain a single mode and minimize optical loss, as well as sufficient physical rigidity and a high glass transition temperature. In the case of perfluoroether applied to the present invention, it is advantageous to achieve a low refractive index, but since the glass transition temperature of the oligomer is usually only -40°C or lower due to the ether structure, the refractive index decreases as the composition ratio of perfluoroether in the resin composition increases, but the secant modulus and tensile strength become relatively low, so in the present invention, the (meth)acrylate reactive group (F 1 This is complemented by fluorinated acrylate oligomers, including 2F 2 : Methoxy (ethoxy) silane reactive group for increasing adhesion to optical device components such as Glass, Si, and SiN Optical element parts are mainly made of SiO 2 The cladding of the optical waveguide formed by TPP3D nanoprinting must have excellent adhesion to such materials. In this case, in the case of low refractive index oligomers containing a large amount of fluorine, the adhesion to other materials tends to be significantly reduced due to the relatively low surface tension and high specific gravity. Therefore, in the present invention, a methoxy(ethoxy)silane reactive group (F 2This is complemented by fluorinated acrylate oligomers, including 3F 3 A hydrocarbon group with 2 to 40 carbon atoms in which some of the hydrogen (H) bonds to the carbon are replaced with oxygen (O) or nitrogen (N). In order to improve the dissolving power of the TPP photoinitiator and to increase the glass transition temperature of the optical waveguide clad formed by TPP 3D nanoprinting, a methyl group (-CH 3 ), the glass transition temperature is only 8°C, but in the case of a carboxyl group (-COOH), the glass transition temperature increases to 130°C, thereby increasing the glass transition temperature of the fluorinated acrylate oligomer.
[0046] Through various tests to realize the above-mentioned additional properties, the present invention has confirmed that the molar ratios of k, l, m, and n constituting the fluorinated acrylate oligomer in the above-mentioned Chemical Formula 5 are adjusted to be in the ranges of k: 60-80%, l: 2-20%, m: 2-10%, and n: 2-20%, respectively, which are more effective in improving the above-mentioned additional properties.
[0047] Example: Preparation of Fluorinated Acrylate Oligomers In the following examples, before preparing the low refractive index resin composition for TPP nano 3D printing according to the present invention, as described in iii) above, the fluorinated acrylate oligomer contained in the resin composition for the cladding of the optical waveguide to improve its physical properties and to increase its adhesion to the optical element was prepared by changing the detailed composition ratio.
[0048] Example 1 (FAO#1) While maintaining the temperature at 90°C under nitrogen purge, 200g of MIBK was added as a solvent to a three-neck flask, followed by 341.4g (79.0mole%) of 2-perfluorohexylethyl methacrylate monomer, 7.8g (6.0mole%) of 2-hydroxyethyl methacrylate (HEMA), 9.9g (4.0mole%) of 3-(trimethoxysilyl)propyl methacrylate, and 9.6g (11.0mole%) of methacrylic acid, and 2,2'-azobisisobutyronitrile (AIBN) as a thermal initiator at 1% relative to the total acrylate monomer, and the monomer mixture was added dropwise using a dropping funnel for 1 hour. After 10 hours of reaction, 1,500 ppm of MEHQ stabilizer was added, followed by 9.31 g of 2-methacryloyloxyethyl isocyanate in an equimolar ratio with HEMA, and 3 drops of DBTDL, and the urethane reaction was allowed to proceed until all NCO reactive groups were consumed. After the urethane reaction was completed, the temperature was maintained at 85°C and the solvent (MIBK) was distilled off under a vacuum atmosphere to produce a fluorinated methacrylate oligomer containing 6.0 mole% methacrylic reactive groups, 4.0 mole% trimethoxysilane, and 11.0 mole% carboxylic acid groups.
[0049] The prepared fluorinated methacrylate oligomer was confirmed to be in a solid phase at room temperature and to have a refractive index of 1.375.
[0050] Example 2 (FAO#2) While maintaining the temperature at 90°C under nitrogen purge, 200g of MIBK was added as a solvent to a three-neck flask, followed by 315.5g (73.0mole%) of 2-perfluorohexylethyl methacrylate monomer, 15.6g (12.0mole%) of 2-hydroxyethyl methacrylate (HEMA), 9.9g (4.0mole%) of 3-(trimethoxysilyl)propyl methacrylate, and 9.6g (11.0mole%) of methacrylic acid, and 2,2'-azobisisobutyronitrile (AIBN) as a thermal initiator at 1% relative to the total acrylate monomer, and the monomer mixture was added dropwise using a dropping funnel for 1 hour. After 10 hours of reaction, 1,500 ppm of MEHQ stabilizer was added, followed by 18.3 g of 2-methacryloyloxyethyl isocyanate in an equimolar ratio with HEMA, and 3 drops of DBTDL, and the urethane reaction was allowed to proceed until all NCO reactive groups were consumed. After the urethane reaction was completed, the temperature was maintained at 85°C and the solvent (MIBK) was distilled off under a vacuum atmosphere to produce a fluorinated methacrylate oligomer containing 12.0 mole% methacrylic reactive groups, 4.0 mole% trimethoxysilane, and 11.0 mole% carboxylic acid groups.
[0051] The prepared fluorinated methacrylate oligomer was confirmed to be in a solid phase at room temperature and to have a refractive index of 1.380.
[0052] Example 3 (FAO#3) While maintaining the temperature at 90°C under nitrogen purge, 200g of MIBK was added as a solvent to a three-neck flask, followed by 332.8g (77.0mole%) of 2-perfluorohexylethyl methacrylate monomer, 15.6g (12.0mole%) of 2-hydroxyethyl methacrylate (HEMA), 9.6g (11.0mole%) of methacrylic acid, and 2,2'-azobisisobutyronitrile (AIBN) as a thermal initiator at 1% of the total acrylate monomer, and the monomer mixture was dropped using a dropping funnel for 1 hour. After reacting for 10 hours, 1,500ppm of MEHQ stabilizer was added, followed by 18.3g of 2-methacryloyloxyethyl isocyanate in an equimolar ratio with HEMA, and 3 drops of DBTDL were added, and the urethane reaction was carried out until all NCO reactive groups were consumed. After the urethane reaction was completed, the temperature was maintained at 85° C. and the solvent (MIBK) was completely removed under vacuum to produce a fluorinated methacrylate oligomer containing 12.0 mole % methacrylic reactive groups, 0.0 mole % trimethoxysilane, and 11.0 mole % carboxylic acid groups.
[0053] The prepared fluorinated methacrylate oligomer was confirmed to be in a solid phase at room temperature and to have a refractive index of 1.376.
[0054] The fluorinated methacrylate oligomers (FAO#1, FAO#2, FAO#3) prepared according to the above-mentioned examples were mixed with 8 wt% of 2-perfluorohexylethyl methacrylate monomer and CP-4 photocuring initiator, respectively, to form a film with a thickness of 1 mm. The film was cured using a UV curing machine, and the secant modulus was measured using a universal testing machine (UTM). The results are shown in Table 2 below.
[0055] [Table 2]
[0056] As shown in Table 2, it was confirmed that the fluorinated methacrylate oligomer prepared in the examples can effectively improve the secant modulus of the resin composition.
[0057] Manufacturing of low refractive index resin composition for TPP nano 3D printing Finally, using each of the fluorinated methacrylate oligomers (FAO#1, FAO#2, FAO#3) prepared according to the above-mentioned Examples, resin compositions (Preparation Examples 1 to 3) were prepared by mixing 20 wt% of the fluorinated methacrylate oligomer (FAO#1, FAO#2, or FAO#3), 50 wt% of DMO, which is a perfluoroether oligomer, 29 wt% of 2-perfluorohexylethyl methacrylate, which is a fluorinated monomer for cosolvent, and 1 wt% of a benzylamine-based photoinitiator (initiator#2), which is a photoinitiator for the TPP reaction. The prepared resin compositions were formed into films with a thickness of 1 mm and cured using a UV curing machine. The physical properties of the preparation examples, including the secant modulus, refractive index, and glass adhesion, were measured using a universal testing machine (UTM).
[0058] The physical properties of the preparation examples prepared by mixing the fluorinated methacrylate oligomer and the fluorinated monomer according to the present invention are compared with the physical properties of a commercially available perfluoroether oligomer (DMO) as shown in Table 3 below.
[0059] [Table 3]
[0060] As shown in , all of the low refractive index resin compositions for TPP nano 3D printing produced by the present invention (Production Examples 1 to 3) exhibit excellent dissolving power for the photoinitiator for the TPP reaction, and it can be confirmed that they have a high secant modulus of 300% to 400% or more compared to DMO consisting only of perfluoroether oligomers.
[0061] In addition, it was found that Preparation Examples 1 and 2, which contain fluorinated methacrylate oligomers (FAO #1 and FAO #2) containing 6% and 12% methoxy(ethoxy)silane reactive groups, respectively, to increase adhesion to optical device components such as glass, Si, and SiN, have nearly 10 times the adhesion to glass compared to Preparation Example 3, which contains no silane reactive groups, or DMO. As mentioned above, it can be confirmed that including silane reactive groups in an appropriate range when constructing a fluorinated acrylate oligomer is an important condition for improving adhesion to optical devices.
[0062] 3D Nanoprinting Testing To test the suitability of the low refractive index resin composition prepared according to the present invention for TPP nano 3D printing, TPP nano 3D printing was performed using a GT from Nanoscribe, Inc., with a lens of x63 magnification and a laser of 30 mW power. After printing a regular hexahedron with each corner of 4 μm, the size of the printed 3D structure was measured through SEM photography, and the results are shown in Table 4 below.
[0063] [Table 4]
[0064] As shown in Table 4, the printed 3D structures showed a fabrication error of less than 0.1 to 0.2 μm in all directions, confirming that the TPP nano 3D printing has sufficient performance for use in forming photonic wire bonding (PWB).
[0065] The present invention also provides a photonic wire bonding (PWB) method that uses the TPP nano 3D printing resin composition having such a composition to directly print an optical waveguide clad surrounding a single-mode optical waveguide in a photonic integrated circuit (PIC) on a substrate by 3D nano printing, thereby minimizing optical loss and fabricating a highly reliable photonic integrated circuit (PIC).
[0066] That is, as already briefly explained above, the conventional photonic wire bonding (PWB) method used to connect optical elements involves dropping a high-refractive index waveguide core resin between optical elements, printing an optical waveguide that optically connects the optical elements in a single mode using a 3D nano printer, then dropping a low-refractive index cladding resin again to cover the entire printed photonic wire (PW, i.e., optical waveguide) and a part of the optical element to be interconnected, and then UV curing. As a result, when dropping the cladding resin or during the curing process of the dropped cladding resin, defects such as damage to the optical waveguide or changes in the connection position often occur due to the load, surface tension, and / or contraction force during the curing process of the dropped cladding resin.
[0067] This is a problem that occurs when a conventional resin for low refractive index cladding, such as the perfluoroether oligomer exemplified above, is used to form only the core part of an optical waveguide as a photonic wire (PW) by a TPP reaction, as it is difficult to realize a two-photon photopolymerization (TPP) reaction due to its insufficient solubility in a photoinitiator for TPP, and then a resin for low refractive index cladding is simply dropped around the core part to be cured, thereby preparing a PIC. As already described in detail above, the present invention provides a resin composition for optical waveguide cladding, which improves the solubility of a photoinitiator for TPP by mixing a fluorinated monomer with a conventional low refractive index fluorinated oligomer for cladding. Hereinafter, an effective photonic wire bonding (PWB) method that can be usefully applied to the preparation of an optical integrated circuit (PIC) using the resin composition for optical waveguide cladding of the present invention will be described in more detail with reference to the attached drawings.
[0068] FIG. 1 is a schematic diagram showing the core 20 and claddings 10 and 30 of an optical waveguide formed by connecting optical elements constituting an optical integrated circuit (PIC) by a photonic wire bonding (PWB) method according to the present invention. In forming a photonic wire bonding (PWB) between optical elements according to the present invention, first, the above-mentioned low refractive index resin composition for TPP reaction according to the present invention is applied between optical elements mounted on a circuit board, and then cured by selective light irradiation using a 3D nanoprinter to print a lower cladding 10 that serves to fix the connection portion with the optical element while guiding the area where the optical waveguide core 20 connected between the optical elements is printed.
[0069] At this time, as shown in FIG. 1, fixing hooks 100 are formed on both ends of the lower clad 10 printed on the substrate to increase the attachment area with the interconnected optical elements, thereby helping to maintain a stronger connection between the optical elements and the PWB connecting the optical elements.
[0070] Once printing of the lower clad 10 is complete, the applied low refractive index resin composition is washed away, and a high refractive index resin for the optical waveguide core is applied and then hardened by selective light irradiation using the 3D nanoprinter, thereby printing the optical waveguide core 20 in the optical waveguide core printing area formed on the upper part of the lower clad 10.
[0071] At this time, the optical waveguide core 20 printed in this manner is composed of a central core portion 20a and tapered portions 20b provided on both sides of the core portion 20a, as shown in FIG. 2. Here, the core portion 20a may be formed into a circular or other various cross-sectional shapes, and is preferably formed to a thickness in the range of 1 μm to 5 μm in order to maintain a single mode.
[0072] In addition, the tapered portion 20b is a section for forming a connection structure with the core portion 20a according to the size and shape of the optical element connection portion depending on the structure of the optical element to be connected, and various structures can be set depending on the length of the optical waveguide to be printed, the refractive index of the core, the refractive index of the cladding, and the wavelength form of the optical signal to be transmitted.
[0073] Once printing of the optical waveguide core 20 is complete, the high refractive resin for the core that was also applied is washed and removed, and the low refractive resin composition for TPP reaction according to the present invention is applied again, and then cured by selective light irradiation using a 3D nanoprinter to print the upper clad 30 on the upper part of the lower clad 10 and the optical waveguide core 20, and then washed and dried to complete the formation of a photonic wire bonding (PWB, i.e., optical waveguide) that connects between optical elements.
[0074] At this time, fixing hooks 100 are formed on both ends of the upper clad 30 printed on the upper part of the lower clad 10 and the optical waveguide core 20 to increase the attachment area with the interconnected optical elements, as shown in FIG.
[0075] In addition, in the process of printing the upper clad 30 by selective light irradiation using a 3D nanoprinter, the light irradiation area is extended to a certain depth below the upper surface of the lower clad 10 and the upper clad 30 is photo-cured, thereby effectively preventing the occurrence of a gap between the upper clad 30 and the lower clad 10 due to alignment errors in the printing position that may occur during the printing process.
[0076] At this time, the extension range of the above-mentioned irradiation region differs depending on the alignment error range of the 3D nanoprinter used, but typically a few μm (1 to 2 μm) is sufficient.
[0077] In addition, the optical waveguide clad formed by combining the upper clad 30 and the lower clad 10 may have various shapes depending on the shape and structure of the optical waveguide core and the optical element, and it is preferable that the total thickness of the clad formed is at least 20 μm or more in order to provide structural stability of the photonic integrated circuit (PIC).
[0078] After the printing of the optical waveguide core and the cladding surrounding it is completed through the above-mentioned process, a post-curing process is performed using additional light irradiation on the photonic wire bonding (PWB) formed on the substrate to completely cure the PWB and complete the fabrication of the photonic integrated circuit (PIC).
[0079] Although the present invention has been described above through some representative embodiments, the embodiments of the present invention described as examples merely show some cases of preferred embodiments of the present invention, and the present invention is not limited thereto, and the scope of protection of the present invention is limited by the matters described in the claims below. Furthermore, it goes without saying that a person having ordinary skill in the art to which the present invention belongs can implement various modifications without changing the gist of the present invention as claimed in the claims, and such modifications and improvements fall within the scope of protection of the present invention as long as their scope is within the scope of matters obvious to a person having ordinary skill in the art to which the present invention belongs. [Industrial Applicability]
[0080] As described above, the low refractive index resin composition for optical waveguide cladding manufactured according to the present invention and the photonic wire bonding (PWB) method using the same have the advantage that the optical waveguide core connecting the optical element mounted on the circuit board and the optical waveguide cladding surrounding the core can all be printed using a 3D nanoprinter by a TPP-based photonic wire bonding (PWB) method using light irradiation, thereby dramatically improving the accuracy and reliability of the photonic integrated circuit (PIC) manufactured thereby. [Explanation of symbols]
[0081] 10: Lower clad, 20: Optical waveguide core 20a: core portion, 20b: tapered portion 30: Upper clad, 100: Fixed hook
Claims
1. 30 to 70 wt % perfluoroether oligomer; 8-30 wt % of fluorinated monomer; 10 to 40 wt % of a fluorinated (meth)acrylate oligomer; and 0.5-2.0 wt % of photoinitiator for TPP reaction; A low refractive index resin composition for TPP nano 3D printing, comprising:
2. The low refractive index resin composition for TPP nano 3D printing according to claim 1, wherein the perfluoroether oligomer has a structure of the following Chemical Formula 1: 【Chemistry 1】 Where: R 1 Each independently represents a hydrocarbon (CH 2 ) 2 to 10 (meth)acrylate groups; R 2 are each independently -CH 2 O- or -CH 2 (O.C.H. 2 CH 2 ) a O- (a is an integer of 1 to 3), R 3 represents an aromatic or aliphatic hydrocarbon group having 6 to 20 carbon atoms; R 4 are each independently -CH 2 --, --CH 2 CH 2 - or -CH 2 (O.C.H. 2 CH 2 ) a - (a is an integer from 1 to 10), m, o, p, q and r are the repeat numbers for each repeat unit, m and o are 1 to 6; r is from 1 to 5,000; p is 1 to 20; The ratio of p to q (p / q) ranges from 0.8 to 2.
5.
3. The low refractive index resin composition for TPP nano 3D printing according to claim 1, characterized in that the fluorinated monomer has a fluorine content of 30 to 60 wt %.
4. The fluorinated monomer is 2,2,2-Trifluoroethyl Acrylate, 2,2,2-Trifluoroethyl Methacrylate, 2,2,3,3-2,2,3,3,3-Pentafluoropropyl Methacrylate, 2,2,3,3-Tetrafluoropropyl Methacrylate, 2,2,3,3-Pentafluoropropyl Methacrylate 1H,1H,5H-Octafluoropentyl Acrylate, 1H,1H,5H-Octafluoropentyl Methacrylate, 1,1,1,3,3,3-Hexafluoroisopropyl Acrylate, 2,2,3,4,4,4-Hexafluorobutyl Methacrylate Methacrylate), 1,1,1,3,3,3-Hexafluoroisopropyl Methacrylate, 2,2,3,3,4,4,4-Heptafluorobutyl Methacrylate, 1H,1H,2H,2H-Nonafluorohexyl Acrylate, 1H,1H,2H,2H-Nonafluorohexyl Methacrylate Methacrylate), 2,2,3,3,4,4,5,5,6,6,7,7-dodecafluoroheptyl acrylate (2,2,3,3,4,4,5,5,6,6,7,7-Dodecafluoroheptyl Acrylate, 2,2,3,3,4,4,5,5,6,6,7,7-Dodecafluoroheptyl Methacrylate, 1H,1H,2H,2H-Tridecafluoro-n-octyl Acrylate, 1H,1H,2H,2H-Tridecafluoro-n-octyl Methacrylate The low refractive index resin composition for TPP nano 3D printing according to claim 3, characterized in that the aryl group is selected from the group consisting of 1,6-bis(acryloyloxy)-2,2,3,3,4,4,5,5-octafluorohexane, ...
5. The photoinitiator for the TPP reaction is The low refractive index resin composition for TPP nano 3D printing according to claim 1, wherein the initiator is selected from the group consisting of bis-triazole-based initiators, benzylamine-based initiators, aminostyryl-triazine-based initiators, imidazole-based initiators, benzyl morpholino phenyl-based initiators, bengal-based initiators, erythrosine-based initiators, isopropylthioxane-based initiators, thienyl coumarin-based initiators, and diphenyl phosphine-based initiators.
6. The low refractive index resin composition for TPP nano 3D printing according to claim 1, wherein the fluorinated (meth)acrylate oligomer has a structure of the following chemical formula 5: 【Chemistry 2】 Where: k, l, m, and n are constants each having a value between 0 and 10,000; R is -H, -CH 3 or a hydrocarbon group having 20 or less carbon atoms, R f is fluorinated carbon (-CF 2 -, -CF 3 ) is a fluorinated carbon group having 2 to 40 carbon atoms, F 1 is a hydrocarbon group having 2 to 40 carbon atoms containing at least one (meth)acrylate, vinyl or epoxy reactive group, F 2 is a methoxy reactive group (-OCH 3 ) or an ethoxy reactive group (—OCH 2 CH 3 ), F 3 is a hydrocarbon group that does not react in a urethane bonding reaction and has 2 to 40 carbon atoms, in which some of the bonded hydrogens (H) are replaced with oxygen (O) or nitrogen (N).
7. The molar ratios of k, l, m, and n are adjusted in the ranges of k: 60 to 80%, l: 2 to 20%, m: 2 to 10%, and n: 2 to 20%, respectively. Low refractive index resin composition for TPP nano 3D printing according to claim 6.
8. 30 to 70 wt % of a fluorinated siloxane oligomer having the structure of Chemical Formula 2 below: 8-30 wt % of fluorinated monomer; 10 to 40 wt % of a fluorinated (meth)acrylate oligomer; and 0.5-2.0 wt % of photoinitiator for TPP reaction; A low refractive index resin composition for TPP nano 3D printing, comprising: 【Chemistry 3】 Where: R 1 Each independently represents a hydrocarbon (CH 2 ) 2 to 10 (meth)acrylate groups; R 2 represents a hydrogenated or fluorocarbon group having 2 to 20 carbon atoms; R 3 is an alkoxysilane group having 1 to 5 silicon atoms; l, m, n and o are repeat numbers for each repeat unit and all range from 1 to 5,000.
9. A photonic wire bonding (PWB) method for forming an optical waveguide for connecting optical elements mounted on a circuit board using a two-photon polymerization (TPP) reaction, Applying a low refractive index resin composition for TPP reaction between optical elements mounted on a circuit board, and then selectively curing the resin composition by light irradiation using a 3D nanoprinter to form a lower clad that fixes a connection portion with the optical element while guiding an area where an optical waveguide core that is connected between the optical elements is printed; After the formation of the lower clad is completed, the applied low refractive index resin composition is washed away, and a high refractive index resin for an optical waveguide core is applied, and then the high refractive index resin is selectively cured by light irradiation using a 3D nano printer to print an optical waveguide core on the upper part of the lower clad. After the printing of the optical waveguide core is completed, the applied high refractive resin is washed and removed, and a low refractive resin composition for TPP reaction is applied again, and then the resin composition is selectively cured by light irradiation using a 3D nano printer to form an upper clad on the upper part of the lower clad and the optical waveguide core; A TPP reaction-based photonic wire bonding (PWB) method comprising:
10. In the step of forming the lower cladding and the upper cladding, 10. The photonic wire bonding (PWB) method according to claim 9, wherein fixing hooks are formed at both ends of the lower clad and the upper clad to increase an attachment area with an optical element to which the optical waveguide is connected.
11. The optical waveguide core is 10. The TPP reaction-based photonic wire bonding (PWB) method of claim 9, comprising a central core portion and a pair of tapered portions provided on both sides of the core portion to form a connection structure between the core portion and a connection portion of an optical element.
12. The core portion is The TPP reaction-based photonic wire bonding (PWB) method of claim 11, formed to a thickness in the range of 1 μm to 5 μm.
13. In the step of forming the upper cladding, 10. The photonic wire bonding (PWB) method according to claim 9, wherein the light irradiation area is extended to a certain depth below the upper surface of the lower clad to perform photo-curing of the upper clad.
14. 10. The TPP reaction-based photonic wire bonding (PWB) method of claim 9, wherein the thickness of the optical waveguide clad formed by combining the upper and lower clads is at least 20 [mu]m.
15. After the step of forming the upper cladding, The TPP reaction-based photonic wire bonding (PWB) method according to claim 9, further comprising the step of: after cleaning and drying the circuit board, performing a post-curing process by additional light irradiation on the photonic wire bonding (PWB) formed on the board.
Citation Information
Patent Citations
Optical waveguide preparation method and device
CN106199830A
Suspended optical waveguide and preparation method thereof
CN111061009A
Organic optical waveguide preparation method based on embedded 3D printing
CN112848282A
Fabrication of optical interconnect structures for a photonic integrated circuit
US20180314151A1
Optical fiber-to-chip interconnection
US20210286140A1